2018
DOI: 10.15537/smj.2018.2.21942
|View full text |Cite
|
Sign up to set email alerts
|

The role of non-invasive ventilation used immediately after planned extubation for adults with chronic respiratory disorders

Abstract: Objectives:To estimate the benefits of non-invasive ventilation (NIV) used immediately after planned postextubation in patients with chronic respiratory disorders.Methods:Cochrane Library, PubMed, the Chinese BioMedical Literature Database of clinical trials (CBD) and Embase were searched for pertinent studies by 2 trained investigators. Pooled odds ratios and 95% confidence intervals (CIs) were calculated by employing both fixed-effects and random-effects models.Results:Eight studies enrolling 736 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…We had extubated our patient after two days of invasive mechanical ventilation and post-extubation the patient required NIPPV over a prolonged period of time. Extubation to NIV is also beneficial in recovery profile and outcome in restrictive lung disease associated with kyphoscoliosis [12]. However a fairly prolonged course of NIPPV had to be instituted before our patients could be shifted to oxygen support by facemask.…”
Section: Discussionmentioning
confidence: 98%
“…We had extubated our patient after two days of invasive mechanical ventilation and post-extubation the patient required NIPPV over a prolonged period of time. Extubation to NIV is also beneficial in recovery profile and outcome in restrictive lung disease associated with kyphoscoliosis [12]. However a fairly prolonged course of NIPPV had to be instituted before our patients could be shifted to oxygen support by facemask.…”
Section: Discussionmentioning
confidence: 98%
“…Herein, NPPV contributed to a reduction in the reintubation rate compared to that observed with COT, without reducing mortality, which is consistent with several previous pairwise systematic reviews comparing NPPV and COT use. Previous RCTs show that NPPV is more effective in reducing reintubation and mortality rates than COT in a high-risk group of patients with post-extubation respiratory failure, including COPD [ 7 , 45 , 46 ]. However, Kondo et al showed that NPPV decreased reintubation and mortality rates more effectively than COT despite the complete exclusion of patients with COPD from the study [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zhou et al showed that NPPV was associated with reductions in mortality and post-extubation respiratory failure rates compared to COT. COPD is a risk factor for reintubation after extubation and predisposes patients to hypercapnia during SBT [ 46 ]. Thus, NPPV is more effective than COT for patients with hypercapnia after extubation [ 50 ], which possibly led to differences in results between our study and that of Zhou et al Furthermore, including trials with many patients with COPD potentially increased the patient heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, NPPV contributed to a reduction in the reintubation rate compared to that observed with COT, without reducing mortality, which is consistent with several previous pairwise systematic reviews comparing NPPV and COT. Previous RCTs show that NPPV is more effective in reducing reintubation and mortality rates than COT in a high-risk group of patients with post-extubation respiratory failure, including COPD [7] [ [43][44]. However, Kondo et al showed that NPPV decreased reintubation and mortality rates more effectively than COT despite the complete exclusion of COPD patients from the study [45].…”
Section: Discussionmentioning
confidence: 99%